I really need help, thanks.
I really need help, thanks. - 1

Answers

Answer 1
Answer: Hello,
I suppose the function is y=3√(6x+42)

==>6x+42>=0 (it must be a square root of a positive)
==>6x>=-42
==>x>=-42/6
==>x>=-7

ANSWER D


Related Questions

What number should both sides of the following equation be divided by to solve for x?(6.4) x = 32 A.4 B.6.4 C.6 D.5
Pls Help I will mark brainliest.
Consider the equation 5x+7=22What two operations are represented in this equation?? How would you "undo" each of those operations Which operation should you "undo" first why?? Please I need help
| 3x | = 9 | -3r | = 9 b/5 = 1
Question:twice as much as the sum of eighteen and elevenin numbers and don't solve

I wwant to no what is 23f

Answers

It's a number that is 23 times the size of ' f ' .

Scott has $500 in the bank. He withdraws the same amount of money each week for 12 weeks, at which point he has $20 left in the bank. How much money did he withdraw each week?

Answers

Scott knew that the only chance we would have to answer this problem would be if he kept his money in a bank that pays no interest, so that's what he did.  The bank simply stored his money in a mayonnaise jar under a tightly-guarded mattress, and he was allowed to come in and take some out of it each week.

He started with $500. He withdrew (500 - 20) = $480 in 12 weeks.

So he must have come in and picked up 480/12 = $40 each week.

Evaluate the function below for x=2.   F(x)=2x^3-x^2-5x+6

Answers

Answer:

A Function states an equation that has only one answer for y for every x. Also, a function assigns exactly one output to each input of a specified type.

i,e y= f(x) where x represents the input variable and y represents the output value.

Given the function: F(x) = 2x^3-x^2-5x+6

Substitute the given input value of x =2 , we get;

F(2) = 2(2)^3-(2)^2-5(2)+6

F(2) = 2(8)-4-10+6

or

F(2) = 16-4-10+6

Simplify:

F(2) = 8

Therefore, the function F(x)=2x^3-x^2-5x+6 for x=2, we have F(2) =8.

f(x)=2x^3-x^2-5x+6 \ \ \ \boxed{x=2}\n \n f(2)=2*2^3-2^2-5*2+6\n \n f(2)=16-4-10+6\n \n f(2)=8

Find the value of t in the equation t+5+3t=1

Answers

t+5+3t=1\nt+3t+5=1\n4t+5=1\n4t+5-5=1-5\n4t=1-5\n4t =-4\n\n\boxed{\bf{t=-1}}
First combine like terms.  1t+3t=4t
5+4t=1
Now subtract 5 from both sides.
4t=-4
Now divide both sides by 4.
t=-1
To check,  let's plug in -1 for t.
-1+5+3*-1=
3*-1=-3
-1+5+-3=1
t=-1

Solve x^2 - 8x + 3 = 0 by completing the square. Which equation is used in the process? (x - 4)^2 = 0 (x - 4)^2 = 13 (x - 4)^2 = 19 Match the following items by evaluating the expression for x = -3

Answers

Answer:

(x -4)^2 = 13

Step-by-step explanation:

To solve this  equation using the completing the square method;

x^2 - 8x + 3 = 0

The first step is to take +3 to the right-hand side of the equation, 3 becomes negative when it crosses over the equality sign.

The equation becomes;

x^2 - 8x  =  -3

The next step is to add square of  half of the coefficient of x to both-side of the equation. That is; you will add   (-4)^2 to both-side of the equation.

x^2 - 8x  +  (-4)^2=  -3 +  (-4)^2

Then, we factorize  the left hand side of the equation and our equation

(x - 4)^2   =    -3 +  (-4)^2

The we simplify the right-hand side of the equation

(x - 4)^2   =  -3 +  16

(x - 4)^2   =  13

Hello,
Answer B

x²-8x+3=0
==>x²-2*4*x+16-13=0
==>(x-4)²=13

What is not the sum to 13

Answers

Answer:

Step-by-step explanation:

3 plus 3 is not 13